UNIQUE PROPERTIES OF ZnO QUANTUM RINGS - Manaselyan, A.Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Electronic states and optical transitions of a ZnO quantum ring containing few interacting electrons in an applied magnetic field are found to be very different from those in a conventional semiconductor system, such as a GaAs ring. Strong Zeeman and Coulomb interactions of the ZnO system, exert a profound influence on the electron states and on the optical properties of the ring. In particular, our results indicate that the Aharonov– Bohm effect in a ZnO quantum ring strongly depends on the electron number.
Keywords: quantum ring, Aharonov–Bohm effect